Pembuatan Produk Nutrisi dan MPASI melalui Pemanfaatan Sumber Daya Alam Daun Kelor (Moringa oleifera) sebagai Langkah Mengatasi dan Mencegah Stunting di Desa Selong Belanak - Elvio Lailatul Jannah; Aenun Jariah; Ayu November; I Gede Ferry Yasa; Iffa Khoirinnisak Fathimatuzzahra; Made Darma Dwipa; Mandala Erlangga Indra Permadi; Maulia Anisa Sabilla; Muhammad Alfain Hidayat; Ni Luh Putu Riana Damayanti; Novaliya Nurma Khafifah (Universitas Mataram, 2023)
Selong Belanak village is located in west Praya sub-district, Central Lombok Regency. Based on the survey results, three main problems were found in this village, namely stunting, disasters and waste management. One of the three existing problems, Stunting is the main topic that really needs to be addressed because the number of cases is still high. The problem of stunting is caused by a lack of socialization about the importance of nutrition for pregnant women which has an impact on the children they are carrying as well as children and toddlers who are included in the stunting category. Based on these problems, the Stunting theme KKN group is trying to carry out programs to prevent and overcome stunting problems. One of them is a work program in the form of producing Nutritional Products/MPASI through utilization of moringa leaves natural resources which play a role in stunting. This work program was compiled after conducting observations and interviews with community leaders in Selong Belanak village. It is hoped that through one of the programs, namely the manufacture of Nutrition/MPASI products through the utilization of moringa Leaf natural resources, it can reduce stunting cases in Selong Belanak village.